PENGARUH SKEPTISISME PROFESIONAL, INDEPENDENSI, DAN PENGALAMAN AUDITOR TERHADAP KETEPATAN PEMBERIAN OPINI AUDIT - Suparmin Suparmin (LPPM University 17 Agustus 1945 Samarinda, 2021)
Pengaruh Skeptisisme Profesional, Independensi, dan Pengalaman Auditor Terhadap Ketepatan Pemberian Opini Audit, This study aims to find evidence of the influence of professional skepticism, independence, and experience of auditors on the accuracy of giving audit opinions. The population in this study were respondents who worked at public accounting firms in Tangerang and South Tangerang. The sampling technique used in this research is convenience sampling, with a total sample of 141 respondents. The statistical method uses Multiple Regression Analysis, with hypothesis testing F test (simultaneous) and T test (partial).The results of this study indicate that professional skepticism, independence, and experience of auditors have a significant effect on the accuracy of giving audit opinions to public accounting firms in Tangerang and South Tangerang.